Changes in Bone Metabolism in Morbidly Obese Patients After Bariatric Surgery: A Meta-Analysis - Liu, Cong; Wu, Dan; Zhang, Jing-Fan; Xu, Duo; Xu, Wan-Feng; Chen, Yu; Liu, Bing-Yang; Li, Ping; Li, Ling (Obesity surgery, 2016)
Background The aim is to evaluate via meta-analysis bone metabolism and bone mineral density (BMD) in morbidly obese patients before and after bariatric surgery. Methods We searched Medline, EMBASE, and the Cochrane Library for relevant studies published before January 2014. The following outcomes were evaluated: serum calcium, serum parathyroid hormone (PTH), serum 25-hydroxyvitamin D [25(OH)D], serum or urinary N-telopeptide (NTX), bone-specific alkaline phosphatase (BSAP), and bone mineral density (BMD). Results Ten studies, including 344 patients, met our inclusion criteria. Results showed a significant decrease in serum calcium (MD = −0.10, 95 %CI −0.14 to −0.07, P < 0.00001) and increase in serum PTH (MD = 12.41, 95 %CI 6.51 to 18.31, P < 0.00001) but no significant difference in serum 25(OH)D (MD = 1.35, 95 %CI −1.12 to 3.83, P = 0.28) following bariatric surgery. There were significant increases in serum or urinary NTX (MD = 18.49, 95 %CI 3.33 to 33.66, P = 0.02) and BSAP (MD = 7.47, 95 %CI 0.21 to 14.72, P = 0.04) but a significant decrease in BMD (MD = −0.08, 95 %CI −0.13 to −0.04, P < 0.00001) after bariatric surgery. Conclusion BMD was significantly decreased, while bone turnover was elevated, and bone remodeling was accelerated following bariatric surgery. Basal bone metabolism should be evaluated preoperatively. To prevent secondary hyperparathyroidism and bone loss, calcium and vitamin D should be monitored closely and supplemented accordingly after the surgery.